2016
DOI: 10.1556/018.67.2016.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity and sodicity stresses on physiological response and productivity inHelianthus annuus

Abstract: Soil salinity and sodicity (alkalinity) are serious land degradation issues worldwide that are predicted to increase in the future. The objective of the present study is to distinguish the effects of NaCl and Na 2 CO 3 salinity in two concentrations on the growth, lipoxygenase (LOX) activity, membrane integrity, total lipids, yield parameters and fatty acids (FAs) composition of seeds of sunflower cultivar Sakha 53. Plant growth, LOX activity and malondialdehyde (MDA) content were reduced by salts stresses. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…However, SFA unchanged in the most genotypes under limited irrigation while it was dependent on the stress level and the genotype under salinity in most of the genotypes. In accordance with our results, Farghaly et al (2016) indicated that salinity also increased SFA and PFA while decreased MFA in sunflower.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, SFA unchanged in the most genotypes under limited irrigation while it was dependent on the stress level and the genotype under salinity in most of the genotypes. In accordance with our results, Farghaly et al (2016) indicated that salinity also increased SFA and PFA while decreased MFA in sunflower.…”
Section: Discussionsupporting
confidence: 93%
“…as well as seed and oil yields per fed were adversely affected by reducing irrigation (I2 and I3) and salinity stress (S1 and S2). Yield reduction in sunflower by drought and salinity stress was observed also by Hassan et al (2011) and Farghaly et al (2016). Our results revealed that the genotypes which showed the better growth under stress levels showed better yield and vis-versa.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Hussain et al, 2018), wheat (Feizi et al, 2007), maize (Baghel et al, 2019;K. Kumar et al, 2017), barley (Tavakkoli et al, 2011), and sunflower (Farghaly et al, 2016;Flowers & Colmer, 2015) was reported with increased soil salinity.…”
Section: Introductionmentioning
confidence: 96%